Qualitative interview study on the Umeå Rainbow Group within the Church of Sweden - Mäkinen, Elina (My University, 2024)
This study investigates the Church of Sweden’s Umeå Rainbow Group, in Northern Sweden. Originating in 2012 as an engaging group for mainly lay volunteers, the Rainbow Group has currently been institutionalised as part of regional Umeå Pastorat. The objective of this study is to research the Church of Sweden’s LGBTQ+ affirming lived religiosity as it is operating within the Rainbow Group. This study sheds light on the Rainbow Group’s actions, challenges and future objectives. This study is founded upon qualitative interview data that was compiled in Umeå in 2019. This data was analysed by following Braun & Clarke’s (2006) thematic analysis. The results illuminate the Rainbow Group’s work as multi-sided enterprises. The Rainbow Group engages in vigorous theological education and queer theology seminars, and takes part in Pride parades and other activities, like ‘drop-in’ weddings. The results indicate that the Rainbow Group’s challenges have altered over the years. The Rainbow Group’s start was shaded by its lacking legitimacy. After becoming institutional part of the Umeå Pastorat, the Rainbow Group is now challenged by its declining volunteer base. The Rainbow Group kindles hope in re-vitalising as a solidarity group for its laymembers. Institutionally, the Rainbow Group calls for more communal, collective and systematically done LGBTQ+ affirming strides in the Church of Sweden. This study contributes to queer religiosity dialogue in sociology, gender studies and the study of religion in contemporary academia. This study may perhaps facilitate the Church of Sweden in their assertions about creating a welcoming church for everyone in Umeå.
Keywords: The Church of Sweden, lived religion, LGBTQ people, qualitative study, study of religion